USM SIGNS MOU WITH UNIVERSITIES IN JAPAN TO ENHANCE COOPERATION IN PEACE RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
TOKYO, JAPAN, 22 February 2016 Universiti Sains Malaysia (USM) today signed two Memorandums of Understanding (MoUs) with two universities in Japan to enhance cooperation in the field of peace research.